2011
DOI: 10.1002/gj.1247
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde metamorphism of ultrahigh‐temperature granulites from the khondalite belt in Inner Mongolia, North China Craton: evidence from aluminous orthopyroxenes

Abstract: Orthopyroxene-sillimanite-sapphirine-spinel-quartz granulites have been reported from the khondalite belt in Inner Mongolia, North China Craton (NCC), which record ultrahigh-temperature (UHT) metamorphism. These rocks record metamorphic temperatures up to 10508C and pressures up to 10 kbar during the peak metamorphism, as indicated by diagnostic UHT mineral assemblages such as equilibrium orthopyroxene þ sillimanite þ quartz, sapphirine þ quartz and low-Zn-spinel þ quartz. To well constrain the retrograde P-T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Thus, Harley (2008) suggested that the assemblage of spinel + quartz should not be used as a diagnostic assemblage for UHT metamorphism and the composition of spinel should be checked carefully especially for Zn, Cr, V, Ti, Ni and Fe 3+ . As an indicative assemblage, spinel + quartz was reported in many cases where other diagnostic UHT assemblages are present, such as from the UHT rocks in Madurai Block of southern India (Tsunogae and Santosh, 2006), the Highland Complex in Sri Lanka (Sajeev and Osanai, 2004), Tuguiwula in the North China Craton Liu et al, 2008Liu et al, , 2010Liu et al, , 2011Santosh et al, 2007aSantosh et al, , 2009), among other examples. These spinels are characterized by low concentration of ZnO (b2.5 wt.%) and Cr 2 O 3 (b0.63 wt.%), and low X Fe 3+ value (Fe 3+ /Fe 3+ +Fe 2+ b 0.15) and could therefore stabilize under UHT conditions.…”
Section: Uht Metamorphism Of Heling'er Spl-grt-sil-bearing Gneissesmentioning
confidence: 94%
“…Thus, Harley (2008) suggested that the assemblage of spinel + quartz should not be used as a diagnostic assemblage for UHT metamorphism and the composition of spinel should be checked carefully especially for Zn, Cr, V, Ti, Ni and Fe 3+ . As an indicative assemblage, spinel + quartz was reported in many cases where other diagnostic UHT assemblages are present, such as from the UHT rocks in Madurai Block of southern India (Tsunogae and Santosh, 2006), the Highland Complex in Sri Lanka (Sajeev and Osanai, 2004), Tuguiwula in the North China Craton Liu et al, 2008Liu et al, , 2010Liu et al, , 2011Santosh et al, 2007aSantosh et al, , 2009), among other examples. These spinels are characterized by low concentration of ZnO (b2.5 wt.%) and Cr 2 O 3 (b0.63 wt.%), and low X Fe 3+ value (Fe 3+ /Fe 3+ +Fe 2+ b 0.15) and could therefore stabilize under UHT conditions.…”
Section: Uht Metamorphism Of Heling'er Spl-grt-sil-bearing Gneissesmentioning
confidence: 94%
“…1; e.g. Guo et al, 2012;Liu et al, 2010Liu et al, , 2011Santosh et al, 2006Santosh et al, , 2007aSantosh et al, ,b, 2009aSantosh et al, ,b, 2012Shimizu et al, 2013;Tsunogae et al, 2011). This implies that the Khondalite Belt might be a Paleoproterozoic hot orogen.…”
Section: Introductionmentioning
confidence: 90%
“…Location Studies 2 Pikwitonei granulite terrane/Sipiwesk Lake, Canada Kooijman et al (2012) 9 Lewisian Complex, Mainland Scotland ; Johnson et al (2012); Zirkler et al (2012) 10 Rogaland Anorthosite Complex, Norway Drüppel et al (2013) 11 Bamble Sector, Norway Kihle et al (2010) 12 Gruf Complex, Italy Galli et al (2011Galli et al ( , 2012 Central Kola Granulite-Gneiss area (Kola Peninsula, Russia) Dolivo-Dobrovol'skii et al (2013) 14 KurskeBesedino block, Voronezh Crystalline Massif, Russia Pilugin et al (2009) 18 North China Craton, China Santosh et al (2007aSantosh et al ( , 2009bSantosh et al ( , 2012Santosh et al ( , 2013; Liu et al (2010Liu et al ( , 2011Liu et al ( , 2012; Peng et al (2010); ; Jiao et al ( , 2013a; ; Guo et al (2012); Wan et al (2013); Yang et al (2014) 19 Odesan area (Gyeonggi Massif), South Korea Oh and Kusky (2007) 20 Higo metamorphic terrane, Japan Osanai et al (1998Osanai et al ( , 2006; Oh and Kusky (2007) 21 Kontum Massif, central Vietnam Nakano et al (2007a,b, 2013 Eastern Ghats Province, India Bose et al (2006); Bose and Das (2007); Das et al (2011); Dharma Rao and Chmielowski (2011); Korhonen et al (2011Korhonen et al ( , 2013aKorhonen et al ( ,b, 2014; Dharma Rao et al (2012) 22 Eastern Ghats belt (Ongole Domain of Krishna Province) ; …”
Section: Nomentioning
confidence: 98%